Peace journalism and the usage of online sources - Ylva Rodny-Gumede (Communicare)
This article looks at reporting practices in the South African news media with regard to online sources and the realisation of peace journalism. Based on data collected from questionnaires and interviews with journalists, media scholars and media monitors in South Africa, the article explores their responses to suggestions that Internet sources are more politically biased than are traditional sources and determines both the extent to which journalists use them and the extent to which they should rely on online sources. The discussion around online sources and potential bias and even hate speech is linked up with normative ideas and debates around peace journalism in the South African news media and the promise of peace journalism through the usage of alternative news sources.